High-voltage sodium ion positive electrode material and preparation method and application thereof

By using a high-voltage sodium ion positive electrode material combined with a P2 core and an O3 outer core in sodium ion batteries, combined with an oxide coating, the problem of material instability of sodium ion batteries at high voltage is solved, and high capacity is achieved , high voltage and long cycle characteristics are suitable for energy storage and electric vehicle markets.

CN119297258AActive Publication Date: 2025-01-10HUNAN MEITE XINCAILIAO SCI & TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411783596.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-01-10
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The material of sodium ion batteries is unstable at high voltages, resulting in poor circulation performance and ineffective application.

Method used

A high-voltage sodium ion positive electrode material combined with a P2 core and an O3 outer core is prepared through co-precipitation reaction and spray drying, combined with an oxide coating to improve the structural stability and conductivity of the material.

Benefits of technology

It realizes high capacity, high voltage and long cycle characteristics, suitable for energy storage and electric vehicle markets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297258A_ABST
    Figure CN119297258A_ABST
Patent Text Reader

Abstract

The invention provides a high-voltage sodium ion positive electrode material as well as a preparation method and application thereof. The chemical general formula of the high-voltage sodium ion positive electrode material is Na < x > Ni Mn M < c > O < 2 >-Na < y > Ni < d > Fe < e > Mn < f > N < g > O < 2 >-M < e >, wherein Na < x > Ni Mn M < c > O < 2 > is a P2 type inner core, Na < y > Ni < d > Fe < e > Mn < f > N < g > O < 2 > is an O < 3 > type outer core, and M < e > is a coating substance. The material characteristic with high voltage can be obtained through the P2-type inner core, the P2-type inner core is further coated with the O3-type outer core, high capacity can be provided through specific cooperation of the inner core and the outer core, meanwhile, the structure stability of the inner core can be kept, and the surface of the outer core is further coated with a layer of oxide, so that the performance of the capacitor is improved. The sodium carbonate can react with the residual sodium source on the surface, reduces the residual sodium on the surface, is beneficial to the processing performance of the material, effectively protects the surface of the material, and enables the material to have the characteristics of high capacity, high voltage and long cycle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials, and in particular to a high-voltage sodium ion positive electrode material and a preparation method and application thereof. Background Art

[0002] Since the commercialization of lithium cobalt oxide lithium batteries, lithium-ion batteries have become the most popular secondary batteries on the market. However, with the large-scale commercialization of lithium-ion batteries, especially the rapid development of electric vehicles in recent years, the problem of insufficient lithium resources has become increasingly serious. The shortage of lithium resources has seriously restricted its large-scale application, so the development of new key materials is urgent. Sodium and lithium belong to the same family of elements and have the same chemical properties. The working principle of sodium ions is similar to that of lithium ions. Compared with lithium-ion batteries, they have obvious advantages. First, sodium is very abundant and low in price, which has obvious cost advantages. Second, the electrode potential of sodium ions is higher than that of lithium ions, which makes its electrolyte system have a lower decomposition potential and high safety. Therefore, the development of sodium-ion batteries is imperative.

[0003] In the sodium-ion battery system, the influence of the positive electrode material on the performance plays an important role. Therefore, the requirements for the sodium-ion positive electrode material are relatively high. It is hoped that the sodium-ion positive electrode material has a high specific capacity; the crystal structure has stability during the embedding and de-embedding process; it provides a fast ion diffusion channel for sodium ions; and has high electronic conductivity.

[0004] The energy density of sodium-ion batteries can be improved in two ways. One way is to increase the specific capacity of the material, and the other way is to increase the voltage of the material. Increasing the voltage can quickly increase the specific capacity of the material, thereby meeting the energy requirements of sodium-ion batteries. However, the material is very unstable under high voltage, and the metal ions of sodium ions are prone to slip, resulting in irreversible phase changes, resulting in very poor cycle performance and inability to be effectively applied. Summary of the invention

[0005] Based on this, it is necessary to provide a high-voltage sodium ion positive electrode material with high stability under high voltage and good cycle performance.

[0006] A high voltage sodium ion positive electrode material, the general chemical formula of which is Na x Ni a Mn b M c O2-Na y Ni d Fe e Mn f N g O2@Me; among them, Na x Ni a Mn b Mc O2 is a P2 type core, Na y Ni d Fe e Mn f N g O2 is an O3 type outer core, Me is a coating material, the mass ratio of the P2 type inner core to the O3 type outer core is 15-20:1, 0.68≤x≤0.72, 0.8≤y≤0.92, a+b+c = d+e+f+g=1, 0.2≤a≤0.5, 0.3≤b≤0.6, 0.05≤c≤0.2, 0.2≤d≤0.3, 0.1≤e≤0.3, 0.3≤f≤0.6, 0.05≤g≤0.2, M is one or more of Zr, Al, B, Fe, Li, Ti, Mg, Co, Y, W, Sr, La, Sr, N is one or more of Li, Ti, B, Mg, Co, Mo, Cu, Y, W, Sr, La, Sr; Me is one or more of silicon oxide, calcium oxide, strontium oxide, titanium oxide, zirconium oxide, yttrium oxide, iron oxide, tungsten oxide, manganese oxide, and nickel oxide.

[0007] In one embodiment, M is one or more of Mg, Co, Li, and Fe, N is one or more of Cu and Ti, and Me is one or more of manganese oxide, yttrium oxide, silicon oxide, strontium oxide, and zirconium oxide.

[0008] In one of the embodiments, in the general chemical formula, M is Mg, N is Cu, 0.38≤a≤0.42, 0.48≤b≤0.52, 0.08≤c≤0.12, 0.28≤d≤0.3, 0.18≤e≤0.22, 0.3≤f≤0.32, 0.18≤g≤0.2, and Me is silicon oxide and strontium oxide with a mass ratio of 1:2.

[0009] In one of the embodiments, in the general chemical formula, M is Co and Li in a molar ratio of 1:1, N is Cu, 0.48≤a≤0.5, 0.30≤b≤0.32, 0.18≤c≤0.2, 0.28≤d≤0.3, 0.18≤g≤0.2, 0.38≤f≤0.42, 0.08≤g≤0.12, and Me is manganese oxide and yttrium oxide in a mass ratio of 1:2.

[0010] In one embodiment, the thickness of the Me coating is 30~80nm, and the ratio of the mass of the Me to the total mass of the inner core and the outer core is 3.3~6:100. For the positive electrode material of this structure, a higher coating amount is required to obtain a better discharge capacity and cycle retention rate.

[0011] The present invention also provides a method for preparing the high voltage sodium ion positive electrode material, comprising the following steps: The Ni salt, the Mn salt and the M salt are mixed according to the molar ratio and dissolved in water, and ammonia water and alkaline solution are added to carry out a coprecipitation reaction to prepare a core precursor; The core precursor is placed in water, and oxides of nickel, iron, manganese and nitrogen are added according to a molar ratio, mixed evenly and then spray-dried to prepare an outer core-wrapped core precursor; The outer core-wrapped inner core precursor is mixed with a sodium source and then sintered to obtain a sodium battery positive electrode material-a sintered matrix; The sodium-ion cathode material-alkane matrix is ​​mixed with Me and then sintered to obtain the high-voltage sodium-ion cathode material.

[0012] In one embodiment, the outer core-wrapped inner core precursor is mixed with a sodium source and sintered at a temperature of 900-1100° C. for 10-20 hours.

[0013] In one embodiment, the sodium positive electrode material, an alkyl matrix, is mixed with Me and sintered at a temperature of 400-900° C. for 4-10 hours.

[0014] In one embodiment, the sodium source is one or more of sodium hydroxide and sodium carbonate.

[0015] In one embodiment, the coprecipitation reaction is carried out at a temperature of 50-65° C. and a pH of 9-10.

[0016] The present invention also provides a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet contains the above-mentioned high-voltage sodium ion positive electrode material or the high-voltage sodium ion positive electrode material prepared by the above-mentioned preparation method.

[0017] The above solution of the present invention has the following beneficial effects: The present invention adopts a specific P2 type core Na x Ni a Mn b M c O2 can obtain material properties with high voltage, but P2 has low capacity. By wrapping a layer of O3 outer core Na on the basis of P2 inner core, y Ni d Fe e Mn f N gO2, the combination of the two can provide high capacity while maintaining the structural stability of the inner core, and further coat the outer core with a layer of oxide, which can react with residual sodium carbonate or residual sodium hydroxide and other sodium sources on the surface, further reducing the residual sodium on the surface, which is beneficial to the processing performance of the material, and effectively protects the surface of the material, improves the surface structure, and reduces the side reactions between the surface of the material and the electrolyte, so that the material has the characteristics of high capacity, high voltage, and long cycle, and can be widely used in energy storage and two-wheel vehicle markets. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a SEM of the precursor of the outer core encapsulating the inner core in Example 1 of the present invention; Figure 2 TEM of the high voltage sodium ion positive electrode material prepared in Example 1 of the present invention; Figure 3 The figures are a comparison of the cycle retention rates of button-type half-cells assembled with the sodium ion positive electrode materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0019] In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, the following will be described in detail with reference to the accompanying drawings and specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. The reagents and instruments used in the examples are conventionally selected in the art unless otherwise specified. The experimental methods without specific conditions in the examples are implemented according to conventional conditions, such as the conditions described in the literature, books or methods recommended by the manufacturer.

[0021] Example 1 50L of deionized water was added to the reactor, and the temperature of the reactor was controlled at 60°C. Nickel sulfate, manganese sulfate, and magnesium sulfate were dissolved in 10L of deionized water according to the molar ratio of Ni:Mn:Mg=4:5:1 to prepare a metal mixed solution. Then, the metal mixed solution was added to the reactor at 150L / h, ammonia water at 6L / h, and alkali solution at 45L / h, respectively. The pH was controlled at 9.5. After reacting for 3h, Ni was formed after aging, filtering, drying, and sieving. 0.4 Mn 0.5 Mg 0.1 (OH)2 core precursor; The Ni 0.4 Mn0.5 Mg 0.1 5 kg of (OH)2 core precursor was added to 10 kg of water. Nickel oxide, iron oxide, manganese dioxide and copper oxide were added to the mixed core solution in a molar ratio of Ni:Fe:Mn:Cu=3:2:3:2. The solid-liquid ratio was 40%. The solution was fully mixed and then spray dried. The inlet temperature of the spray was 260 ° C and the outlet temperature was 115 ° C. After the spray drying was completed, the outer core was formed to encapsulate the inner core precursor, such as Figure 1 Shown is the SEM of the precursor of the outer core encapsulating the inner core; 1000g of the outer core-wrapped inner core precursor and 480.71g of sodium carbonate were added to a high-speed mixer, and then mixed at a low speed for 5 minutes and then at a high speed for 30 minutes. After the mixing was completed, the materials were placed in a calcination pot, placed in a box furnace, sintered at 950°C for 15 hours, and then naturally cooled out of the furnace, crushed and sieved to obtain a calcined material; The calcined material and strontium oxide were added to a high-speed mixer and mixed. The weight of strontium oxide accounted for 3.8% of the mass of the calcined matrix. After high-speed mixing for 30 minutes, the material was placed in a calcined pot, put into a box furnace and sintered at 600℃ for 8 hours, then naturally cooled and taken out of the furnace. After crushing and sieving, a high-voltage sodium ion positive electrode material Na 0.69 Ni 0.4 Mn 0.5 Mg 0.1 O2-Na 0.88 Ni 0.3 Fe 0.2 Mn 0.3 Cu 0.2 O2@SrO, Figure 2 The figure shows the TEM of the sodium ion positive electrode material prepared in this example. The coating thickness is 42 nm, and the mass ratio of the P2 type inner core to the O3 type outer core is 15:1.

[0022] The obtained sodium ion positive electrode material, conductive agent SP and PVDF were weighed in a mass ratio of 90:5:5, and the solid content was added in a ratio of 45%, wherein the concentration of PVDF glue was 8%, and the sodium ion positive electrode material coating slurry was evenly dispersed by centrifugal high-speed stirring, and evenly coated on aluminum foil with a small coating machine. After high-temperature baking at 120°C, a dry electrode was obtained. After rolling, the electrode was cut into a 14 mm diameter electrode, and a button half-cell was assembled with a sodium sheet as a negative electrode, a ceramic fiber as a diaphragm, and a 1 mol / L NaPF6 (EMC+PC+FEC (2%)) solution as an electrolyte. The test voltage was 2.0~4.35V. After testing, the first discharge capacity of this embodiment was 145.3mAh / g, and the 50-week cycle retention rate was 94.5%, which shows that it has the characteristics of high capacity, high voltage and long cycle.

[0023] Example 2 50L of deionized water was added to the reactor, and the temperature of the reactor was controlled at 60°C. Nickel sulfate, manganese sulfate, cobalt sulfate, and lithium sulfate were dissolved in 10L of deionized water according to the molar ratio of Ni:Mn:Co:Li=5:3:1:1 to prepare a metal mixed solution. Then, the metal mixed solution was added to the reactor at 150L / h, ammonia water at 6L / h, and alkali solution at 45L / h, respectively. The pH was controlled at 9.5. After reacting for 3h, Ni was formed after aging, filtering, drying, and sieving. 0.5 Mn 0.3 Co 0.1 Li 0.1 (OH)2 core precursor; The Ni 0.5 Mn 0.3 Co 0.1 Li 0.1 5 kg of (OH)2 core precursor was added to 10 kg of water, and nickel oxide, iron oxide, manganese dioxide and copper oxide were added to the mixed core solution in a molar ratio of Ni:Fe:Mn:Cu=3:2:4:1. The solid-liquid ratio was 40%. The solution was fully mixed and then spray-dried. The inlet temperature of the spray was 260°C and the outlet temperature was 115°C. After spray drying, a precursor of the core wrapped in an outer core was formed. 1000g of the outer core-wrapped inner core precursor and 490.89g of sodium carbonate were added to a high-speed mixer, and then mixed at a low speed for 5 minutes and then at a high speed for 30 minutes. After the mixing was completed, the materials were placed in a calcination pot, placed in a box furnace, sintered at 950°C for 15 hours, and then naturally cooled and taken out of the furnace, and crushed and sieved to obtain a calcined material; The calcined material, manganese oxide and yttrium oxide are added to a high-speed mixer for mixing. The weight of manganese oxide and yttrium oxide accounts for 5.0% of the mass of the calcined matrix, and the mass ratio of manganese oxide to yttrium oxide is 1:2. After high-speed mixing for 30 minutes, the material is placed in a calcined pot, put into a box furnace for sintering at 600°C for 8 hours, and then naturally cooled out of the furnace. After crushing and sieving, a high-voltage sodium ion positive electrode material Na 0.68 Ni 0.5 Mn 0.3 Co 0.1 Li 0.1 O2-Na 0.92 Ni 0.3 Fe 0.2 Mn 0.4 Cu 0.1 O2@MnO-Y2O3, the coating thickness is 60nm, and the mass ratio of the P2 type inner core to the O3 type outer core is 18: 1. According to the test method of Example 1, the first discharge capacity is 150.2mAh / g, and the 50-week cycle retention rate is 94.8%, which shows that it has the characteristics of high capacity, high voltage and long cycle.

[0024] Example 3 50L of deionized water was added to the reactor, and the temperature of the reactor was controlled at 60°C. Nickel sulfate, manganese sulfate, and iron sulfate were dissolved in 10L of deionized water according to the molar ratio of Ni:Mn:Fe=3:6:1 to prepare a metal mixed solution. Then, the metal mixed solution was added to the reactor at 150L / h, ammonia water at 6L / h, and alkali solution at 45L / h, respectively. The pH was controlled at 9.5. After reacting for 3h, Ni was formed after aging, filtering, drying, and sieving. 0.3 Mn 0.6 Fe 0.1 (OH)2 core precursor; The Ni 0.3 Mn 0.6 Fe 0.1 5 kg of (OH)2 core precursor was added to 10 kg of water, and nickel oxide, iron oxide, manganese dioxide and titanium oxide were added to the mixed core solution in a molar ratio of Ni:Fe:Mn:Ti=2:2:5:1. The solid-liquid ratio was 40%. The solution was fully mixed and then spray-dried. The inlet temperature of the spray was 260°C and the outlet temperature was 115°C. After spray drying, a precursor of the core wrapped in an outer core was formed. 1000g of the outer core-wrapped inner core precursor and 460.32g of sodium carbonate were added to a high-speed mixer, and then mixed at a low speed for 5 minutes and then at a high speed for 30 minutes. After the mixing was completed, the materials were placed in a calcination pot, placed in a box furnace, sintered at 950°C for 15 hours, and then naturally cooled and taken out of the furnace, and crushed and sieved to obtain a calcined material; The calcined material, zirconium oxide and yttrium oxide were added to a high-speed mixer for mixing. The weight of zirconium oxide and yttrium oxide accounted for 5.9% of the mass of the calcined matrix. The mass ratio of zirconium oxide to yttrium oxide was 2:3. After high-speed mixing for 30 minutes, the material was placed in a calcined pot, put into a box furnace for sintering at 600°C for 8 hours, and then naturally cooled out of the furnace. After crushing and sieving, a high-voltage sodium ion positive electrode material Na 0.68 Ni 0.3 Mn 0.6 Fe 0.1 O2-Na 0.90 Ni 0.2 Fe 0.2 Mn 0.5 Ti 0.1 O2@ZrO2-Y2O3, the coating thickness is 50nm, and the mass ratio of the P2 type inner core to the O3 type outer core is 20: 1. According to the test method of Example 1, the first discharge capacity is 143.2mAh / g, and the 50-week cycle retention rate is 95.1%, which shows that it has the characteristics of high capacity, high voltage and long cycle.

[0025] Example 4 This embodiment is basically the same as embodiment 1, except that the weight of the coating accounts for 2.9% of the mass of the alkane matrix. The test is carried out according to the test method of embodiment 1, and the first discharge capacity is 140.2 mAh / g, and the 50-week cycle retention rate is 89.4%.

[0026] Comparative Example 1 50L of deionized water was added to the reactor, and the temperature of the reactor was controlled at 60°C. Nickel sulfate, manganese sulfate, and magnesium sulfate were dissolved in 10L of deionized water according to the molar ratio of Ni:Mn:Mg=4:5:1 to prepare a metal mixed solution. Then, the metal mixed solution was added to the reactor at 150L / h, ammonia water at 6L / h, and alkali solution at 45L / h, respectively. The pH was controlled at 9.5. After reacting for 3h, Ni was formed after aging, filtering, drying, and sieving. 0.4 Mn 0.5 Mg 0.1 (OH)2 core precursor; The Ni 0.4 Mn 0.5 Mg 0.1 5 kg of (OH)2 core precursor was added to 10 kg of water. Nickel oxide, iron oxide, manganese dioxide and copper oxide were added to the mixed core solution in a molar ratio of Ni:Fe:Mn:Cu=3:2:3:2. The solution was fully mixed and then spray dried. The inlet temperature of the spray was 260°C and the outlet temperature was 115°C. After spray drying, a precursor of the core wrapped in an outer core was formed. After adding 1000g of the precursor of the outer core wrapped inner core and 480.71g of sodium carbonate into a high-speed mixer, mixing was performed at a low speed for 5min and then at a high speed for 30min. After mixing, the materials were placed in a calcination pot and sintered at 950°C in a box furnace for 15h, then naturally cooled and taken out of the furnace. The high-voltage sodium ion positive electrode material was crushed and sieved to obtain the high-voltage sodium ion positive electrode material. The test was performed according to the test method of Example 1. The first discharge capacity was 137.2mAh / g, and the 50-week cycle retention rate was 88.5%, and the cycle performance was poor.

[0027] Comparative Example 2 50L of deionized water was added to the reactor, and the temperature of the reactor was controlled at 60°C. Nickel sulfate, manganese sulfate, and magnesium sulfate were dissolved in 10L of deionized water according to the molar ratio of Ni:Mn:Mg=4:5:1 to prepare a metal mixed solution. Then, the metal mixed solution was added to the reactor at 150L / h, ammonia water at 6L / h, and alkali solution at 45L / h, respectively. The pH was controlled at 9.5. After reacting for 3h, Ni was formed after aging, filtering, drying, and sieving. 0.4 Mn 0.5 Mg 0.1 (OH)2 core precursor; The Ni 0.4 Mn 0.5 Mg 0.1 After 1000g of (OH)2 core precursor and 458.68g of sodium carbonate were added into a high-speed mixer respectively, they were first mixed at a low speed for 5 minutes and then at a high speed for 30 minutes. After the mixing was completed, the materials were placed in a calcination pot and put into a box furnace for sintering at 950°C for 15 hours, then naturally cooled and taken out of the furnace. The high-voltage sodium positive electrode material was crushed and sieved to obtain the high-voltage sodium battery positive electrode material. The test was carried out according to the test method of Example 1. The initial discharge capacity was 136.5mAh / g, and the 50-week cycle retention rate was 81.9%, and the cycle performance was poor.

[0028] Comparative Example 3 This comparative example is basically the same as Example 1, except that the outer core is replaced by another O3 type outer core: Na 0.88 Ni 0.4 Fe 0.3 Mn 0.3 O2. The test was carried out according to the test method of Example 1, and the first discharge capacity was 133.1 mAh / g, and the 50-week cycle retention rate was 80.5%.

[0029] Comparative Example 4 This comparative example is basically the same as Example 1, except that the core is replaced with another P2 core: Na 0.69 Ni 0.4 Mn 0.6 O2. The test was carried out according to the test method of Example 1, and the first discharge capacity was 135.3 mAh / g, and the 50-week cycle retention rate was 79.8%.

[0030] Example 4 The method is basically the same as that in Example 1, except that the composition and proportion of Me are changed to prepare different sodium ion positive electrode materials. The test results are shown in Table 1 according to the test method of Example 1.

[0031] Table 1

[0032] As shown in Table 1, for this particular P2-type kernel Na x Ni a Mn b M c O2 and O3 type outer core Na y Ni d Fe e Mn f N gThe cycle retention rate of O2 positive electrode materials can be further improved by optimizing the composition and ratio of the coating. The use of silicon oxide and strontium oxide at a ratio of 1:2 can achieve an excellent 50-week cycle retention rate of 97.1%. However, when inappropriate coatings and ratios such as calcium oxide, silicon oxide and strontium oxide at a ratio of 2:1:2 are used, the discharge capacity and cycle retention rate are significantly reduced.

[0033] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high voltage sodium ion positive electrode material, characterized in that: Its chemical formula is Na x Ni a Mn b M c O2-Na y Ni d Fe e Mn f N g O2@Me; Among them, Na x Ni a Mn b M c O2 is a P2 type core, Na y Ni d Fe e Mn f N g O2 is an O3 type outer core, Me is a coating material, the mass ratio of P2 type inner core to O3 type outer core is 15-20:1, 0.68≤x≤0.72, 0.8≤y≤0.92, a+b+c =d+e+f+g=1, 0.2≤a≤0.5, 0.3≤b≤0.6, 0.05≤c≤0.2, 0.2≤d≤0.3, 0.1≤e≤0.3, 0.3≤f≤0.6, 0.05≤g≤0.2, M is one or more of Zr, Al, B, Fe, Li, Ti, Mg, Co, Y, W, Sr, La, Sr, N is one or more of Li, Ti, B, Mg, Co, Mo, Cu, Y, W, Sr, La, Sr; Me is one or more of silicon oxide, calcium oxide, strontium oxide, titanium oxide, zirconium oxide, yttrium oxide, iron oxide, tungsten oxide, manganese oxide, nickel oxide; The method for preparing the high voltage sodium ion positive electrode material comprises the following steps: The Ni salt, the Mn salt and the M salt are mixed according to the molar ratio and dissolved in water, and ammonia water and alkaline solution are added to carry out a coprecipitation reaction to prepare a core precursor; The core precursor is placed in water, and oxides of nickel, iron, manganese and nitrogen are added according to a molar ratio, mixed evenly and then spray-dried to prepare an outer core-wrapped core precursor; The outer core-wrapped inner core precursor is mixed with a sodium source and then sintered to obtain a sodium battery positive electrode material-a sintered matrix; The sodium-ion cathode material-alkane matrix is ​​mixed with Me and then sintered to obtain the high-voltage sodium-ion cathode material.

2. The high voltage sodium ion positive electrode material according to claim 1, characterized in that: M is one or more of Mg, Co, Li, and Fe, N is one or more of Cu and Ti, and Me is one or more of manganese oxide, yttrium oxide, silicon oxide, strontium oxide, and zirconium oxide.

3. The high voltage sodium ion positive electrode material according to claim 1, characterized in that: In the general chemical formula, M is Mg, N is Cu, 0.38≤a≤0.42, 0.48≤b≤0.52, 0.08≤c≤0.12, 0.28≤d≤0.3, 0.18≤e≤0.22, 0.3≤f≤0.32, 0.18≤g≤0.2, and Me is silicon oxide and strontium oxide with a mass ratio of 1:

2.

4. The high voltage sodium ion positive electrode material according to claim 1, characterized in that: In the general chemical formula, M is Co and Li in a molar ratio of 1:1, N is Cu, 0.48≤a≤0.5, 0.30≤b≤0.32, 0.18≤c≤0.2, 0.28≤d≤0.3, 0.18≤g≤0.2, 0.38≤f≤0.42, 0.08≤g≤0.12, and Me is manganese oxide and yttrium oxide in a mass ratio of 1:

2.

5. The high voltage sodium ion positive electrode material according to claim 1, characterized in that: The thickness of the Me coating is 30-80 nm, and the ratio of the mass of the Me to the total mass of the inner core and the outer core is 3.3-6:

100.

6. A method for preparing the high voltage sodium ion positive electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The Ni salt, the Mn salt and the M salt are mixed according to the molar ratio and dissolved in water, and ammonia water and alkaline solution are added to carry out a coprecipitation reaction to prepare a core precursor; The core precursor is placed in water, and oxides of nickel, iron, manganese and nitrogen are added according to a molar ratio, mixed evenly and then spray-dried to prepare an outer core-wrapped core precursor; The outer core-wrapped inner core precursor is mixed with a sodium source and then sintered to obtain a sodium battery positive electrode material-a sintered matrix; The sodium-ion cathode material-alkane matrix is ​​mixed with Me and then sintered to obtain the high-voltage sodium-ion cathode material.

7. The preparation method according to claim 6, characterized in that: The outer core-wrapped inner core precursor is mixed with a sodium source and sintered at a temperature of 900-1100°C for 10-20 hours; the sodium-based cathode material-alkane matrix is ​​mixed with Me and sintered at a temperature of 400-900°C for 4-10 hours.

8. The preparation method according to claim 6, characterized in that: The sodium source is one or more of sodium hydroxide and sodium carbonate.

9. The preparation method according to claim 6, characterized in that: The coprecipitation reaction is carried out at a temperature of 50-65° C. and a pH of 9-10.

10. A sodium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet contains the high-voltage sodium ion positive electrode material according to any one of claims 1 to 5 or the high-voltage sodium ion positive electrode material prepared by the preparation method according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Sodium-ion battery positive electrode material and preparation method thereof, positive electrode and sodium-ion battery

    CN116741984A

  • Sodium-ion battery positive electrode material and preparation method thereof

    CN117497728A

  • Composite layered oxide positive electrode material, positive electrode plate as well as preparation method and application of composite layered oxide positive electrode material and positive electrode plate

    CN117727887A

  • Doping modified sodium-ion battery precursor as well as preparation method and application thereof

    CN118877952A

  • Positive electrode material, sodium ion battery, and electric device

    WO2024082817A1